MASTER Prompt and Follow-Up GRB Observations - Nataly Tyurina; Vladimir Lipunov; Victor Kornilov; Evgeny Gorbovskoy; Nikolaj Shatskij; Dmitry Kuvshinov; Pavel Balanutsa; Alexander Belinski; Vadim Krushinsky; Ivan Zalozhnyh; Andrey Tlatov; Alexander Parkhomenko; et al. (Advances in Astronomy)
We presented the results of last years GRB observations obtained on the MASTER robotic telescope, which is the only telescope of its kind in Russia. These results include 5 prompt observations of GRB in 2008 and 2009, follow-up observations of 15 other GRBs in 2008-2009, the first observations in different polarization angles of optical emission from the gamma-ray bursts GRB091020, and observations in different polarization angles for GRB091127 and GRB090820.